2004
DOI: 10.3386/w10213
|View full text |Cite
|
Sign up to set email alerts
|

A Portrait of the Artist as a Young or Old Innovator: Measuring the Careers of Modern Novelists

Abstract: Some important novelists have written a great novel early in their careers and have produced lesser works thereafter, whereas others have improved their work gradually over long periods and have made their major contributions late in their lives. Which of these patterns a novelist follows appears to be systematically related to the nature of his work. Conceptual writers typically have specific goals for their books, and produce novels that emphasize plot; experimental writers' intentions are often uncertain, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…For example, despite his strong objection to the generalizations of the psychological research on the poetry-novel difference in peak ages, he has never conducted an investigation looking at both poets and novelists together. Instead, he has put out one working paper on modern American poets (Galenson, 2003) and another on modern novelists (Galenson, 2004). In neither paper does he make direct numerical comparisons with the findings of the other paper.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, despite his strong objection to the generalizations of the psychological research on the poetry-novel difference in peak ages, he has never conducted an investigation looking at both poets and novelists together. Instead, he has put out one working paper on modern American poets (Galenson, 2003) and another on modern novelists (Galenson, 2004). In neither paper does he make direct numerical comparisons with the findings of the other paper.…”
mentioning
confidence: 99%
“…To detect this second outcome requires that the two samples be incorporated into a single quantitative investigation. Fortunately, because Galenson (2003Galenson ( , 2004 published the raw data, this integrative analysis can be performed here. Are there four career trajectories, or just two?…”
mentioning
confidence: 99%
“…In general, it might be more reasonable to assume that the distributions of e i and z i are not independent: high ability (high z i ) individuals may be more efficient in their education (low e i ). While this possibility is not considered formally in this paper, the data set used here considers great inventors, for whom we might take the view that zi is essentially constant 7. Another natural option is a normal distribution, a variation that has no substantive effect on the results.…”
mentioning
confidence: 99%
“…As such, different patterns of creative behaviors may be expected in older versus younger individuals. Originally developed as a theory for understanding the creative behaviors of artists, Galenson (2006a;2006b) observed that individuals could be classified into two overarching categories based on the means by which their most innovative works were developed. The first category, termed "experimental innovators," encapsulates those artists who developed their most creative, and ultimately successful, work through a tentative and prolonged period of learning and discovery.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…For example, Galenson and Kotin (2007) illustrated that an experimental innovator versus conceptual innovator categorization could be applied to movie directors in the film industry. Likewise, an experimental innovator versus a conceptual innovator classification has been successfully applied as a framework for understanding the creative output of older versus younger authors and songwriters (Galenson, 2004;2009b).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%